EMPLOYEE ENGAGEMENT AS MEDIATION OF TALENT MANAGEMENT AND AUTHENTIC LEADERSHIP ON JOB SATISFACTION AT PT. XYZ - Syahrian (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
Abstract: This study aims to analyze the effect of Talent Management and Authentic Leadership on Employee Engagement and Job Satisfaction, as well as to examine the role of Employee Engagement as a mediating variable in these relationships at PT. XYZ. The object of this research is 87 employees of PT. XYZ. The sampling technique used is non-probability sampling with purposive sampling, with data collected through the distribution of questionnaires using a Likert scale. Data analysis was performed using Smart PLS 4.0 to test the hypotheses. The results indicate that Talent Management has a positive effect on Employee Engagement, and Authentic Leadership also positively influences Employee Engagement. Furthermore, Employee Engagement was found to positively affect Job Satisfaction. However, Talent Management does not have a direct effect on Job Satisfaction, although it influences Job Satisfaction through Employee Engagement. In contrast, Authentic Leadership does not have an effect on Job Satisfaction through Employee Engagement.